An Appetite for Wonder The Making of a Scientist - Richard Dawkins (London Black Swan, 2014)
Born to parents who were enthusiastic naturalists, and linked through his wider family to a clutch of accomplished scientists, Richard Dawkins was bound to have biology in his genes. But what were the influences that shaped his life? And who inspired him to become the pioneering scientist and public thinker now famous (and infamous to some) around the world? In An Appetite for Wonder we join him on a personal journey from an enchanting childhood in colonial Africa, through the eccentricities of boarding school in England, to his studies at the University of Oxford's dynamic Zoology Department, which sparked his radical new vision of Darwinism, The Selfish Gene. Through Dawkins' honest self-reflection, touching reminiscences and witty anecdotes, we are finally able to understand the private influences that shaped the public man who, more than anyone else in his generation, explained our own origins.
Keywords: Autobiographies -- Autobiographies; Evolution -- Evolution